Pengaruh Manajemen Terhadap Akreditasi Madrasah Tsanawiyah Se-Kecamatan Tellusiattinge Kabupaten Bone - Aisyah, Siti Aisyah; Damopolii, Muljono; Mania, Sitti (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2020)
This study describes the effect of madrasah’s management Functions on madrasah’s accreditation in Madrasah Tsanawiyah in Tellu Siattinge District, Bone Regency. This type of research is quantitative, by presenting statistical data on the phenomena that occur. The study population was 88 teachers as well as the sample. The technique of collecting data using a questionnaire and analyzed by descriptive statistics and inferential statistics by testing the hypothesis with the product moment correlation test. The results showed that there was a positive and significant effect of madrasah management functions on madrasah accreditation with a coefficient of 0.662 and a significance of 0.000. There is an effect of 66% of the management function on madrasah accreditation and other factors are influenced by other factors. This large percentage should get the attention of educational stakeholders regarding the importance of planning, organizing, implementing, and evaluating functions in improving madrasah accreditation.